Associação de fatores antropométricos e externos na postura de crianças em idade escolar - Jacovoni, Edir Nobre [UNESP] (2016)
The spinal column is located on the rear and middle trunk portion. It consists of 33 vertebrae (7 cervical, 12 thoracic, 5 lumbar, 5 sacral and 4 coccygeal). In upright posture the man has curvatures that are critical to the biomechanics of the spine (cervical lordosis, thoracic kyphosis, lumbar lordosis and sacral kyphosis). The knee is middle joint of the more complex lower extremity biomechanics in terms of simple and functional terms, composed of bones: the femur, tibia, fibula and patella. The foot consists of 26 bones and is divided anatomically into three segments: Rearfoot; midfoot; forefoot. The correct posture is the position in which a minimum stress is applied to each joint. The postural changes are defined as the result of the opposing forces acting on the joint surfaces and the excess request of muscles and ligaments, since the position is not governed by only one isolated muscle but by set of muscles, then depends on the harmony thereof. Postural assessment is a very important step for physical therapy, because from this evaluation builds up the kinesiological diagnosis and guide to the therapeutic procedures. The photogrammetry is constituted as simple, low cost, little time of application, easy photo interpretation, high reproducibility, no radiation and can be applied several times throughout the individual's growth. There is a means of diagnosis, but is presented as useful method for analysis of postural asymmetries.